2016
DOI: 10.1016/j.ijsu.2016.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Image guided radiofrequency ablation for small renal masses

Abstract: The diagnosis of incidental small renal masses (SRM) has increased during the past two decades secondary to the increased use of various abdominal imaging modalities. In the past decade there has been a shift from radical nephrectomy to nephron sparing surgery techniques where partial nephrectomy has become the standard of care. Thermal ablation (TA) modalities such as freezing or heating delivered percutaneously for the treatment of small renal masses (SRM) is now offered in many Institutions as a treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…RFA is based on the generation of heat by means of an alternating electric current used at different frequencies and consequently cell death occurs in the exposed area (9). This alternating electric current is transferred to the tissue with the aid of a probe placed in the center of the target tissue, and these systems are generally monopolar.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
See 2 more Smart Citations
“…RFA is based on the generation of heat by means of an alternating electric current used at different frequencies and consequently cell death occurs in the exposed area (9). This alternating electric current is transferred to the tissue with the aid of a probe placed in the center of the target tissue, and these systems are generally monopolar.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…RFA-induced cellular damage is based on a time-temperature curve where less time is required at higher temperatures (9). In a study, cellular damage was shown to develop after 60 minutes exposure to 45°C, 5 minutes exposure to 55°C, and 1-minute exposure to 70°C (10).…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…With radiofrequency an alternating current determines ionic friction that leads to slow heat generation, with subsequent protein denaturation, blood coagulation, and coagulative necrosis [33, 34]. RFA determines also blood coagulation, thus reducing the bleeding risk in comparison with cryoablation [35].…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, many ablation therapies for abdominal metastatic tumors were used such as radiofrequency ablation (RFA), [6,7] microwave ablation (MWA), [8,9] cryoablation, [10] irreversible electroporation (IRE), [11] and high-intensity focused ultrasound (HIFU). [12,13] Retroperitoneal deep tumors from hepatic, colorectal, renal, prostate, and ovarian carcinomas have important structures like the gastrointestinal tract and large blood vessels around, which may challenge excision, and easily induce serious complications like hemorrhage, intestinal adhesion, and even death after injury.…”
Section: Introductionmentioning
confidence: 99%